Relevance and limits of the Dutch disease in developing countries : the case of natural resources in Africa - (:unkn) unknown (My University, 2022)
This thesis is dedicated to the understanding of the “Dutch disease” theory andits implications for developing countries. To that aim, it questions some of the mainunderlying assumptions of theoretical Dutch disease models, and tests their relevance basedon empirical evidence for resource-rich African countries. The thesis is decomposed into fourchapters. The first chapter reviews the theoretical and empirical literature on Dutch disease,both to show the importance of this concept for developing countries and to highlight itslimitations. Chapter 2 discusses different definitions of real exchange rates and estimate theimpact of oil revenues on five exchange rate indicators in a panel of nine African oilexporting countries between 1995 and 2017. Chapter 3 tries to distinguish the Dutch diseasefrom the pass-through effect by investigating the impact of oil price and production shocks ondomestic inflation in five African countries that are both net oil exporters and oil consumersbetween 1995 and 2019. The final chapter assesses the impact of extractives resources onvalue-added in agriculture, manufacture, construction and services in a panel of 50 Africancountries between 1995 and 2019.
Keywords: African Research